2015
DOI: 10.5037/jomr.2015.6304
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Free Vascularised Bone Flaps for Mandibular Reconstruction: Are Dental Implants Possible?

Abstract: ObjectivesFree fibula flap remains the flap of choice for reconstruction of mandibular defects. If free fibula flap is not possible, the subscapular system of flaps is a valid option. In this study, we evaluated the possibility of dental implant placement in patients receiving a scapular free flap for oromandibular reconstruction.Material and MethodsWe retrospectively reviewed 10 patients undergoing mandible reconstruction with a subscapular system free-tissue (lateral border of the scapula) transfer at the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Currently, there is limited information regarding the osseointegration, radiographic bone loss and success of dental implants in SFF. Previous studies, mainly focusing on radiographic bone loss, showed a relatively high rate of bone resorption in SFF, however the effect of the observed bone loss on dental implants remains uncertain [42,43]. This opens the question as to whether the SFF bone volume is adequate for dental implantation.…”
Section: Dental Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is limited information regarding the osseointegration, radiographic bone loss and success of dental implants in SFF. Previous studies, mainly focusing on radiographic bone loss, showed a relatively high rate of bone resorption in SFF, however the effect of the observed bone loss on dental implants remains uncertain [42,43]. This opens the question as to whether the SFF bone volume is adequate for dental implantation.…”
Section: Dental Rehabilitationmentioning
confidence: 99%
“…One retrospective study found that bone height and width loss in SFF was significant one year after reconstructive surgery, but in this study only six patients received dental implants. Moreover, this study lacked coherence of the study population [42]. A more recent retrospective study, which included five patients with scapula free flaps, compared bone volume loss in several free flaps, but oral rehabilitation based on dental implants was not performed within two years of observation [43].…”
Section: Dental Rehabilitationmentioning
confidence: 99%
“…8 This has been supported by clinical reports. 9 The issue of pedicle length has been addressed with the technical modification which elongates the pedicle by using the angular branch off the thoracodorsal artery. 10 This allows harvest of bone from the scapular tip and a significant length of lateral border.…”
Section: Andmentioning
confidence: 99%
“…A comparative anatomical study, specifically addressing available bone stock as a criteria for dental implantability, demonstrated that the scapula had an average cross‐sectional area comparable to the iliac crest and could support implants in nearly 80% of the cadavers studied . This has been supported by clinical reports . The issue of pedicle length has been addressed with the technical modification which elongates the pedicle by using the angular branch off the thoracodorsal artery .…”
Section: Introductionmentioning
confidence: 99%
“…The bone is also easier to osteotomize than the fibula given that it is thinner and that there is a lower risk of injury to the vascular pedicle during this step. Although it is thinner, the scapular bone can still successfully receive dental implants . Despite all of these advantages, many surgeons prefer not to harvest this flap given the challenges associated with positioning, prepping, and draping, the inability to perform a simultaneous ablation and harvest (2‐team approach), and the short‐term limited shoulder range of motion.…”
Section: Introductionmentioning
confidence: 99%